Pengaruh Persepsi Penilaian Hasil Belajar Terhadap Keyakinan Guru Tentang Pembelajaran Matematika - Nur, Andi Saparuddin; Pratama, Rian Ade; Betaubun, Martha (Edumatica : Jurnal Pendidikan Matematika, 2026)
The paradigm in assessing mathematics learning outcomes has turned, especially after the pandemic and the enactment of the Kurikulum Merdeka. Assessment serves to not only determine learning objectives, but also as a process and tool for learning. Nevertheless, attitudes toward the assessment of mathematics learning outcomes can be mediated by several factors, such as the teachers' conceptions of mathematics learning. This study aims to examine the effect of perceptions of assessments on teachers' beliefs about mathematics learning. This study employed a correlational design involving 69 mathematics teachers from 20 provinces in Indonesia. Student characteristics are classified by gender, educational stage, teaching experience, and highest academic qualification. A Google Form was distributed through WhatsApp groups to obtain data. The data were analyzed using simple analysis, contingency correlation, and SEM analysis. Results indicate that teachers generally continue to use AoL format rather than AfL and AaL in assessing mathematics learning outcomes. The association between differentiation factors and mathematics teachers’ beliefs was generally weak to very weak. School level and teaching experience showed a low correlation with mathematics teachers' beliefs. The mediating role of teachers' beliefs about learning assessment accounted for 32% teachers' beliefs about mathematics learning. This study emphasizes the necessity for educational interventions that promote practical classrooms applications to develop teachers’ attitudes of the importance of AfL and AaL. Future researchers may conduct longitudinal studies with a larger number of participants and a more equal distribution of characteristics to minimize bias and obtain most comprehensive results